Managing the risk of loans with basis risk: sell, hedge, or do nothing? - Larry D. Wall; Milind M. Shrikhande (Federal Reserve Bank of Atlanta, 2000)
Individual loans contain a bundle of risks including credit risk and interest rate risk. This paper focuses on the general issue of banks' management of these various risks in a model with costly loan monitoring and convex taxes. The results suggest that if the hedge is not subject to basis risk, then hedging dominates a strategy of "do nothing." Whether hedging dominates loan sales depends on whether it induces reduced monitoring, the net benefit of monitoring, and the reduced tax burden of eliminating all risk via selling. If the hedge is subject to basis risk, then a "do nothing" strategy may dominate the hedging and loan sales strategy for risk neutral banks. A number of empirical implications follow from the analytical and numerical results in the paper.
Keywords: 330; Loan sales; Hedging (Finance); Risk management